Residual palm kernel expeller as the support material and alimentation provider in enhancing attached microalgal growth for quality biodiesel production - Rawindran, H. (Academic Press, 2022)
Albeit the biodiesel production from suspended microalgal system has gained immense interests in recent years, the domineering limitation of being economically infeasible has hindered this technology from partaking into a large-scale operation. To curtail this issue, attached growth system had been introduced by various studies; however, those were still unable to alleviate the socio-economic challenges faced in commercializing the microalgal biomass production. Thus, this study had developed a novel approach in cultivating-cum-harvesting attached Chlorella vulgaris sp. microalgae, whilst using solid organic waste of palm kernel expeller (PKE) as the supporting and alimentation material for microalgal biofilm formation. The effects of three variables, namely, PKE dosage, light intensity, and photoperiod, were initially modelled and later optimized using Response Surface Methodology tool. The derived statistical models could predict the growth performances of attached microalgal biomass and lipid productivity. The optimum growing condition was attained at PKE dosage of 5.67 g/L, light intensity of 197 μmol/m2 s and photoperiod of 8 light and 16 dark hours/cycle, achieving the microalgal density and lipid content of 9.87 ± 0.05 g/g and 3.39 ± 0.28 g/g, respectively, with lipid productivity of 29.6 mg/L day. This optimum condition had led to the intensification of biodiesel quality with a high percentage of monounsaturated fatty acid, i.e., oleic acid (C18:1), encompassing 81.86 of total fatty acid methyl ester components. Given that the positive acquisition of PKE as an excellent supporting material in enhancing the microalgal density and lipid productivity that had resulted in the commercially viable biodiesel quality, this study served as a novel revolution in augmenting the microalgae and solid waste utilities for sustainable energy generation. © 2022 Elsevier Ltd